KAJIAN RESIKO GEMPA DENGAN PENDEKATAN METODE RAPID VISUAL SCREENING (RVS) FEMA 154 DAN 3D RESPONSE SPEKTRUM TERHADAP GEDUNG UNIVERSITAS WIJAYAKUSUMA PURWOKERTO - Novi Andhi Setyo Purwono; Iwan Rustendi; Roesly Sakban; Ajeng Purba Kencana (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
An earthquake is one that occurs as a result of a sudden shift in the soil layer below the earth's surface. Purwokerto as the city of Banyumas Regency is a city that is currently trying to develop as well as other big cities in Indonesia. The lecture building is a public service facility in terms of education for the community As the lecture building must be able to provide feasibility and comfort so that activities inside and outside the lecture building become comfortable. This aims of the reasearch to assess the vulnerability of several buildings at Wijayakusuma University to earthquakes. To find out the feasibility of the building, the analysis approach was carried out using the RVS method contained in FEMA 154, besides that the load calculation was carried out using SAP 2000 modeling with the 3D Response Spectrum method. The results showed that the multi-storey buildings at the University of Wijayakusuma Purwokerto were safe against earthquakes when assessed by the RVS method, whereas when assessed by the 3D response spectrum method in accordance with SNI 1726-2019 these buildings were less safe for fundamental natural vibration times, but for the third loading the building is safe.